Expression of the mosquitocidal toxins of Bacillus sphaericus and Bacillus thuringiensis subsp. israelensis by recombinant Caulobacter crescentus, a vehicle for biological control of aquatic insect larvae - Thanabalu, T. (2014)
Applied and Environmental Microbiology